The Influence of the Covid 19 Virus and Online Learning on the Education System for Islamic Subjects - Syah Putra, Arman; Disniarti, Disniarti; Oktaviani, Heriyah; Sari, Wulan; Apriani, Luthfiyah (CV. Inara, 2021)
The background of this research is to know the background of the influence of the covid-19 virus and learning online on the education system for Islamic religious subjects whether the covid-19 virus which is now a resident throughout the world affects the learning system in Indonesia, especially subjects Islam and whether online learning media is a very appropriate medium to be applied to the teaching and learning system that exists during the current pandemic. The method used in this research is to use a quantitative method using a survey tool conducted to 100 people who were randomly selected with the survey tool, the data obtained will be able to represent the original data in the field and be able to find out the actual results. The thing that will be found in this research is how to find out the relationship between Covid-19 and the learning system and how this online learning system affects the learning system on Islamic religious subjects. Therefore, what variables affect it can be seen in this study. In this study will produce data that will be able to find out what variables affect Islamic religious subjects, especially the teaching and learning system in Indonesia and what variables affect the current pandemic, therefore variables must be determined carefully and can affect dependent variable. Keyword : The Covid 19 Virus, Online Learning, Education System, Islamic Subjects.